An Experiment on Apparent Specific Gravity and Settleable Degree of Fire Extinguishing Agent according to Durable Years of Regional Powder Extinguisher - Dal, Son, Ju-; Sung, Kong, Ha- (International Journal of Membrane Science and Technology, 2023)
For powder extinguishing agents based on the useful life of the powder extinguisher, a powder extinguisher with a elapsed life of 6-10 years was collected from market, factory, and apartment houses to experiment with changes in volume by appearance and sedimentation, and to examine digestive characteristics. As a result of the study, the first, second, and third arithmetic mean analysis of the apparent specific gravity experiments from 6 to 10 years of use, showed that the total arithmetic average of three experiments in the market area with an 8-year useful life was 127mL. In 2012, the average arithmetic average of three experiments in multi-family housing with a 10-year useful life was 131mL, which was found to be inappropriate. Second, in the experimental value for sedimentation, it was found to be unsuitable in the 2012 sedimentation experiment on samples in the apartment area. In other words, the sedimentation test of the powder extinguishing agent should not occur within an hour, but the sample in the apartment complex area in 2012 was found to be defective. Third, the fire extinguisher needs to be strengthened to enable fire extinguisher maintenance and inspection because problems that cannot be used during initial fire suppression occur depending on the place of deployment, surrounding environment, age of use, and maintenance status.